CRP AND ATHEROSCLEROSIS IN HEMODIALYSIS PATIENTS, A NESTED CROSS-SECTIONAL STUDY - Talia Weinstein T; Doron Schwartz; Idit Schwartz; Mona Boaz (The Korean Society of Nephrology, 2012)
CRP is a recognized marker of systemic inflammation. The degree to which CRP is associated with carotid and/or femoral intima media thickness (IMT), markers of atherosclerosis, may quantify the degree to which inflammation explains cardiovascular disease in patients with end stage renal disease. The purpose of this study was to estimate the association between CRP and both carotid and femoral IMT in hemodialysis (HD) patients. The present cross-sectional study is nested in the Sevelamer hydrochloride and ultrasound-measured femoral and carotid intima media thickness progression in end stage renal disease (SUMMER) clinical trial. Carotid (common, internal and bifurcation) and femoral arteries were visualized in B-mode ultrasonography. CRP was measured in serum. The study cohort included 177 HD patients (39.5% female, mean age 67.8±11.5 years). All measures of both carotid and femoral IMT were significantly, positively associated with CRP. Compared to subjects without, subjects with PVD, coronary revascularization and hypertension had significantly higher CRP levels. Conversely, subjects treated with sevelamer hydrochloride had significantly lower CRP levels than those not exposed to this medication. CRP was significantly, positively associated with serum phosphorus, calcium and PTH, and significantly inversely associated with HDL. In conclusion, CRP is significantly, positively associated with both femoral and carotid IMT and suggests an association between inflammation and atherosclerosis in HD patients.